2011
DOI: 10.1002/mds.23473
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin A versus B in sialorrhea: A prospective, randomized, double-blind, crossover pilot study in patients with amyotrophic lateral sclerosis or Parkinson's disease

Abstract: Either 250 U Dysport or 2500 U Neurobloc have similar effectiveness and safety in controlling sialorrhea. BoNT-B has a shorter latency and comparable duration. Cost analysis, considering the doses used in this study protocol favored BoNT-B treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 38 publications
5
68
2
4
Order By: Relevance
“…Recovery of function from neuromuscular paralysis by botulinum neurotoxins varies according to the serotype and the target tissue, but for BoNT/A, the duration of action is typically 1 to 3 months (Rossetto et al, 2001). BoNT/B had a shorter duration in some (Sloop et al, 1997;Blitzer, 2005) but not all (Pappert et al, 2008;Guidubaldi et al, 2011) studies, whereas recovery from paralysis by BoNT/E was more rapid (Eleopra et al, 1998). The duration of the functional central nervous system (CNS) actions of these toxins is not known, although in one study cleaved SNAP-25 was evident for a prolonged period after intrahippocampal injection of BoNT/A (Antonucci et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of function from neuromuscular paralysis by botulinum neurotoxins varies according to the serotype and the target tissue, but for BoNT/A, the duration of action is typically 1 to 3 months (Rossetto et al, 2001). BoNT/B had a shorter duration in some (Sloop et al, 1997;Blitzer, 2005) but not all (Pappert et al, 2008;Guidubaldi et al, 2011) studies, whereas recovery from paralysis by BoNT/E was more rapid (Eleopra et al, 1998). The duration of the functional central nervous system (CNS) actions of these toxins is not known, although in one study cleaved SNAP-25 was evident for a prolonged period after intrahippocampal injection of BoNT/A (Antonucci et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the effect of BTX in the treatment of hypersalivation generally lasts about 2–4 months,19, 20 our finding suggests that duration of BTXA effect in hypersalivation due to anti‐NMDA receptor encephalitis is similar to that due to other neurological disorders. However, despite these results, its duration in anti‐NMDA receptor encephalitis still remains unclear because hypersalivation is significantly affected by disease activity.…”
Section: Discussionmentioning
confidence: 65%
“…44 BoNT serotypes A and B are considered to be equally efficacious and safe. In a study evaluating the differences between the 2 serotypes, Guidubaldi et al 46 found that BoNT-B has a shorter latency and the same duration of efficacy compared with BoNT-A. However, the costs of the 2 treatments are significantly different: at the doses used in the study, a treatment with BoNT-B costs approximately half that with BoNT-A.…”
Section: Bont (Botox)mentioning
confidence: 99%